2014
DOI: 10.1021/am503745w
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-Induced Synthesis of Various Gold Nanoparticles and Their Heterogeneous Catalytic Properties on a Paper-Based Substrate

Abstract: This work describes the light-induced preparation of various gold nanoparticles and demonstrates their possible use as efficient photothermal heating materials and practical heterogeneous catalysts under the irradiation of a solar-based light after being loaded onto a paper-based substrate. The synthesis of gold nanoparticles was accomplished under the irradiation of daily sunlight and a solar-simulated light with an intensity that was closely adjusted to the one-sun condition. Tunable sizes of gold nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…The functions of gold nanoparticles heavily rely upon their structure, size and morphology, so finding a way to modulate nanoparticles biosynthesis is an important aspect of the research8910. Shape and symmetry-dependent mechanical properties of metallic gold on the nanoscale has already been elucidated by Mahmoud et al 11.…”
mentioning
confidence: 99%
“…The functions of gold nanoparticles heavily rely upon their structure, size and morphology, so finding a way to modulate nanoparticles biosynthesis is an important aspect of the research8910. Shape and symmetry-dependent mechanical properties of metallic gold on the nanoscale has already been elucidated by Mahmoud et al 11.…”
mentioning
confidence: 99%
“…This can be better understood by the fact that recently Bhaduri et al claimed Ag NP synthesis by sunlight [ 98 ]. Similarly, Kim et al showed sunlight based synthesis of gold nanoparticles [ 99 ]. Therefore, what we see here is some studies which claim to achieve the nanoparticle synthesis just like biogenic agents with no requirement of laborious microorganism screening, plant culturing/Soxhlet extraction, cultivating and complex downstream separation processing can be eliminated.…”
Section: Putting Emphasis On Reaction Kinetics and Process Control: Umentioning
confidence: 80%
“…Noteworthy, some novel synthesis strategies, such as biosynthesis [52,53], 2D immiscible oil/water interface [54], levitated leidenfrost drop [55], sunlight-induced synthesis [56] and so on, have been reported, and such green and economic synthesis methods for preparation of uniform and controlled AuNMs provide the opportunity for development of low-cost and sustainable analytical techniques. However, the above technologies need to be further improved and standardized.…”
Section: Synthesis Of Aunmsmentioning
confidence: 99%